Analysis of scatter in the compression properties of fibre-polymer laminates in fire. (15th July 2021) - Loh, T.W.; Khatibi, A.A.; Mouritz, A.P.
Abstract: Previous research has shown that large scatter can occur in the failure loads and failure times of load-bearing fibre reinforced polymer laminates when exposed to fire. This scatter causes uncertainty in quantifying the structural survivability of composite structures in fire. A combined experimental and modelling study is presented to determine the cause of the scatter and to present a statistical-based model to predict the scatter in the structural survivability of laminates under combined compression loading and one-sided heating by fire. Multiple fire-under-load experimental tests are performed under identical conditions to quantify the magnitude of the scatter for a glass-vinyl ester laminate. The scatter to the deformation rate and time-to-failure of the laminate increased when the heat flux or applied compression load were reduced. A model is presented that can predict the scatter to the compressive failure stress and time-to-failure of a fibreglass laminate when subjected to combined fire exposure and compression loading. The analysis reveals that multiple factors cause the scatter, including small variations in the thickness and fibre content of the laminate.